Economic and Political Implications of De-Dollarizing Saudi Oil Transactions: An Analysis of a Panel Quantile Regression Focused on European Union Countries - Dermechi, Feriel; Zakane, Ahmed (Ekonomika, 2025)
This article explores the economic and political implications of de-dollarization in Saudi oil transactions, by focusing on the European Union countries. It examines how an increased euro usage in these transactions influences the real exchange rate of the euro against the dollar and the volume of the oil imports from Saudi Arabia. A new de-dollarization indicator is introduced, measured as the proportion of the total imports denominated in euros relative to the total imports in all currencies. By using panel data from 2000 to 2023 for 13 EU oil-importing countries, the study applies quantile regression to capture heterogeneous effects across the conditional distribution. The findings show that de-dollarization positively and significantly affects the euro’s real exchange rate at all quantiles. However, its impact on oil import volumes varies: it is negative for countries with low to moderate oil dependency (quantiles 0.25 and 0.5) but becomes insignificant for highly oil-dependent countries (quantile 0.75). Key implications for EU countries include: i) adjusting monetary policies to stabilise exchange rates, optimising reserves, and promoting the euro use in energy trade; and ii) strengthening regional energy cooperation and diversifying their supply sources in order to reduce vulnerabilities.
Keywords: de-dollarization in Saudi oil transactions; real exchange rate; EU oil-importing countries; quantile regression